Clinical and Laboratory Justification for the Use of Occlusal Splints in the Treatment of Patients with Pathological Tooth Wear (Literature Review) - Dienha М. П.; Kostiuk Т. М. (Actual Dentistry, 2025)
Abstract. Pathological tooth wear (PTW) is one of the most common forms of non-carious dental hard tissue lesions [4, 6], characterized by excessive loss of enamel and dentin due to abrasive, erosive, attritional, and functional factors. This condition is frequently associated with temporomandibular joint (TMJ) dysfunction [6, 9], neuromuscular imbalance, and disruption of occlusal relationships. These factors significantly affect patients’ quality of life. Nowadays, in prosthetic dentistry, occlusal splints are used as both therapeutic and diagnostic devices in the management of such patients. The purpose of this work is to analyze and evaluate existing data on the effectiveness of the use of occlusal splints in the treatment of patients with pathological tooth abrasion based on the study of world scientific sources recently, which identify the disadvantages and advantages of the use of splint therapy in restoring the functional balance of the dento-maxillary apparatus. Materials and methods. A search for scientific publications was conducted in the PubMed database for the period from 2016 to 2025. Research results and conclusions. Pathological tooth attrition is a multifactorial condition that results from the combined influence of both local and systemic factors. Clinical studies confirm the effectiveness of using occlusal splints in reducing muscle hypertonicity, eliminating temporomandibular joint dysfunctions, and reducing the intensity of further tooth attrition. Modern diagnostic methods, particularly magnetic resonance imaging, teleradiography, and cone-beam computed tomography, enable an objective assessment of morpho-functional changes associated with PSZ. An interdisciplinary approach to treating patients with PSZ is of key importance. The most effective are occlusal splints, which are made considering the characteristics of occlusal relationships, muscle activity, and TMJ function of patients. The widespread use of standard splints without considering the individual parameters of each patient is less effective and may lead to complications. The clinical and laboratory use of occlusal splints is a scientifically sound, effective, and safe method of treating patients with PSS.